The Role of Montage Activities in Improving The Fine Motoric Skills in Early Childhood - Nurafia Nurafia; Eka Damayanti; M. Yusuf T; Dahlia Patiung (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2021)
This study aims at determining the role of montage activities in improving fine motoric skills in the early childhood. It is the type of the library research form using secondary data sources in the document forms such as journals and research results (thesis) that are relevant to the research focus. The data analysis applied data analysis model of Miles and Huberman which consists of data reduction, data display, and conclusion. The results show that the montage activities played a role in improving the fine motoric skills in the early childhood, especially when the children doing cutting, pasting, drawing, and coloring activities. In improving the children’s fine motoric skills, the montage activities are also able to develop imagination, attract the children’s learning interest, and develop the children’s creativity, skills, dexterity, and painstaking attitudes.